DAMPAK IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII MTsN 12 AGAM - Vionita, Vania Hilda (Departemen Matematika, 2024)
Abstract - Once a learning process is complete, the most important item is the learning outcomes. The mathematical achievement of seventh graders at MTsN 12 Agam is dismal. Problems are addressed through the usage of PBL. The purpose of this research is to evaluate the effectiveness of direct instruction with that of Problem Based Learning (PBL) in the context of mathematics education. Non-Equivalent Posttest-Only Control Group Design for descriptive and pseudo-research purposes. Research samples were drawn from two classes at MTsN 12 Agam: VII.D, which served as the experimental class, and VII.A, which served as the control class. Using a t-test, we checked for homogeneity, normality, and hypothesis testing between the two groups of samples. With a P-value of 0.006 and an actual level of 5%, the findings of the test indicate that H0 is rejected. Because of this, children in the experimental group outperform those in the control group on math tests. Thus, the PBL approach affects the mathematical learning results of MTsN 12 Agam seventh graders.Keywords: Model PBL, Learning Outcomes, Direct Learning Model